Establishment of a diverse head and neck squamous cancer cell bank using conditional reprogramming culture methods. Issue 2 (10th January 2023) - Li, Daniel; Thomas, Carlos; Shrivastava, Nitisha; Gersten, Adam; Gadsden, Nicholas; Schlecht, Nicolas; Kawachi, Nicole; Schiff, Bradley A.; Smith, Richard V.; Rosenblatt, Gregory; Augustine, Stelby; Gavathiotis, Evripidis; et al.
Abstract: Most laboratory models of head and neck squamous cell cancer (HNSCC) rely on established immortalized cell lines, which carry inherent bias due to selection and clonality. We established a robust panel of HNSCC tumor cultures using a "conditional reprogramming" (CR) method, which utilizes a rho kinase inhibitor (Y‐27632) and co‐culture with irradiated fibroblast (J2 strain) feeder cells to support indefinite tumor cell survival. Sixteen CR cultures were successfully generated from 19 consecutively enrolled ethnically and racially diverse patients with HNSCC at a tertiary care center in the Bronx, NY. Of the 16 CR cultures, 9/16 were derived from the oral cavity, 4/16 were derived from the oropharynx, and 3/16 were from laryngeal carcinomas. Short tandem repeat (STR) profiling was used to validate culture against patient tumor tissue DNA. All CR cultures expressed ΔNp63 and cytokeratin 5/6, which are markers of squamous identity. Human papillomavirus (HPV) testing was assessed utilizing clinical p16 staining on primary tumors, reverse transcription polymerase chain reaction (RT‐PCR) of HPV16/18‐specific viral oncogenes E6 and E7 in RNA extracted from tumor samples, and HPV DNA sequencing. Three of four oropharyngeal tumors were p16 and HPV‐positive and maintained HPV in culture. CR cultures were able to establish three‐dimensional spheroid and murine flank and orthotopic tongue models. CR methods can be readily applied to all HNSCC tumors regardless of patient characteristics, disease site, and molecular background, providing a translational research model that properly includes patient and tumor diversity.